2017
DOI: 10.2174/1871520616666160526103432
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-loaded Immunoliposomes Functionalized with Trastuzumab: A Strategy to Enhance Cytotoxicity to HER2-positive Breast Cancer Cells

Abstract: Liposomes have been successfully employed in the clinic for several drugs to improve pharmacokinetics and reduce side effects. Furthermore, liposomes can be functionalized with antibodies for targeted delivery to cells that express the antigen. While the monoclonal antibody trastuzumab has been employed in the therapy of HER2-positive breast cancer, the resistance developed during treatment has been widely reported. Drugs, such as rapamycin, a lipophilic mTOR inhibitor, could be used in combination with trastu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
2
11
0
1
Order By: Relevance
“…FKBP1A, also named FKBP12, is a member of the FK-506-binding protein (FKBP) family, and its expression in cells is ubiquitous [43,44]. FKBP1A mediates the immunosuppressive and antitumor effects of rapamycin [45], widely used in the treatment of breast cancer [46,47]. One study on Eph receptors and invasive breast carcinoma suggested that the…”
Section: Plos Onementioning
confidence: 99%
“…FKBP1A, also named FKBP12, is a member of the FK-506-binding protein (FKBP) family, and its expression in cells is ubiquitous [43,44]. FKBP1A mediates the immunosuppressive and antitumor effects of rapamycin [45], widely used in the treatment of breast cancer [46,47]. One study on Eph receptors and invasive breast carcinoma suggested that the…”
Section: Plos Onementioning
confidence: 99%
“…The treatment of breast cancer is complex and relies on several factors, including the type of tumor, tumor size, grade, proliferation rate and lymph node status. Existing treatment methods include surgery, chemotherapy, radiotherapy and hormonal treatments 3 . In recent years, the presence of breast cancer tumor markers has been investigated, and several markers were identi ed, including the estrogen receptor (ER), progesterone receptor (PR) and the human epidermal growth factor receptor 2 (HER2) 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing treatment methods include surgery, chemotherapy, radiotherapy and hormonal treatments 3 . In recent years, the presence of breast cancer tumor markers has been investigated, and several markers were identi ed, including the estrogen receptor (ER), progesterone receptor (PR) and the human epidermal growth factor receptor 2 (HER2) 3,4 . Human epidermal growth factors belong to a family of transmembrane receptor tyrosine kinases (RTKs).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations